Few-step synthesis, thermal purification and structural characterization of porous boron nitride nanoplatelets. (15th November 2016) - Kostoglou, Nikolaos; Lukovic, Jelena; Babic, Biljana; Matovic, Branko; Photiou, Demetris; Constantinides, Georgios; Polychronopoulou, Kyriaki; Ryzhkov, Vladislav; Grossmann, Birgit; Mitterer, Christian; Rebholz, Claus
Abstract: Hexagonal boron nitride (h-BN) nanoplatelets with 99 wt.% purity, 900 to 2000 nm particle width, 30 to 90 nm particle thickness, 213 m 2 /g specific surface area (SSA), 66% micropore SSA and 0.85 nm average pore size were synthesized in a powder form using H3 BO3 and CO(NH2 )2 as precursors followed by consecutive thermal treatments under inert and oxidized atmospheres. Thermal gravimetric analysis (TGA) combined with differential scanning calorimetry (DSC), under synthetic air-flow and up to 1300 °C, were employed to evaluate both purity and oxidation resistance of the product directly upon its synthesis. The h-BN powder was collected at the stage of its highest purity which, based on TGA-DSC data, corresponded to an additional heat treatment up to 700 °C. The active oxidation seems to occur in the temperature range between 860 and 1000 °C, followed by formation of B2 O3 in the final residue. Subsequently, the purified h-BN powder was extensively characterized for its structure, morphology and porosity using X-ray diffraction, scanning electron microscopy and nitrogen gas adsorption/desorption measurements at 77 K, respectively. As briefly discussed, purity and SSA seem to have a crucial role in the thermal stability and oxidation resistance of BN materials in general. Graphical abstract: Highlights: Porous h-BN powders were prepared by mixing H3 BO3 and CO(NH2 )2 followed by pyrolysis in N2 and calcination in air. Purity increased to 99 wt.% at 700 o C, active oxidation initiated at 860 o C and B2 O3 formation completed at 1000 o C. The as-prepared h-BN particles seem to mainly oxidize from their edges, leaving the planar hexagonal surfaces intact. Purified h-BN platelets with large surface area (213 m 2 /g), increased microporosity (66 %) and narrow pore sizes (0.85 nm).